Speaking Anxiety Level of English as Foreign Language in English Education Study Program at STKIP PGRI Sidoarjo - Anggi Febi Jayanti (P-SEMART JOURNAL, 2022)
This study was conducted the speaking anxiety level of English in English Education Study Program Students at STKIP PGRI Sidoarjo. This research described the students’ speaking anxiety level analyzed by using descriptive qualitative research method. The research subjects of this research were English Education students which consisted of 25 active students and the data were questionnaire that used Foreign Language Classroom Anxiety Scale (FLCAS) procedure to elaborate the result of students’ speaking anxiety level in table, percentage, and chart which became the data descriptions. The result showed that 43% of the students tend to have speaking anxiety level which is the score is under 51 which means low of speaking anxiety level. In interview answer, the students stated that many factors troubled them but the students also have their own technique to reduce anxiety such as holding own hands, keep calm, and so forth. Based on these findings, it can be concluded that learning to speak English as a Foreign Language in the classroom is able to make many foreign language students feel nervous and tense so that they are less able to do their best in the speaking class.